(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
Bacterial collagenolytic proteases have drawn increasing attention due to their essential role in the global nitrogen cycling and their virulent role in some diseases. The inhibition of these enzymes is attractive, as it does not attack the pathogen directly but rather blocks the colonization and infiltration of the host by the clostridia. Optically active non-protein α-amino acids have been screened for their ability to inhibit collagenase of Clostridium histolyticum. Both structure-based drug design approach (modeling) and that of determining enzyme activity in the presence of amino acids have been used to identify low molecular weight inhibitors of collagenase. The compounds able to inhibit collagenase activity have been revealed and IC50 values have been estimated.